2019
DOI: 10.1177/0022022119836517
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cultural Values in the Folk Psychiatry Explanatory Framework: A Comparison of Chinese- and Euro-Canadians

Abstract: The Folk Psychiatry (FP) model proposes a process through which people understand mental illness, comprising four dimensions: pathologizing, moralizing, psychologizing, and medicalizing. Cultural group differences have been observed in previous research using part of this model, with one prior study suggesting that adherence to cultural values may partly explain these differences. The current study, therefore, evaluated whether horizontal–vertical and individualism–collectivism values contribute to explaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Despite supporting evidence, options for the systematic assessment of folk psychiatry domains remain limited. Vargas et al (2019) reported the evaluation of moralizing, medicalizing, and psychologizing beliefs using a study-specific scale in participants presented with depression-focused vignettes. However, individual items and the psychometric properties of scores were not provided.…”
Section: Stereotypes and Survivor Impactsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite supporting evidence, options for the systematic assessment of folk psychiatry domains remain limited. Vargas et al (2019) reported the evaluation of moralizing, medicalizing, and psychologizing beliefs using a study-specific scale in participants presented with depression-focused vignettes. However, individual items and the psychometric properties of scores were not provided.…”
Section: Stereotypes and Survivor Impactsmentioning
confidence: 99%
“…Analyses failed to identify meaningful associations with gender, but the extent to which results generalize to more diverse communities-or the intersection of sex, gender, and culture across different populations-remains unknown. Existing research has demonstrated potential cultural variations in causal explanations of depression based on specific social norms and the valuation of social hierarchies (Vargas et al, 2019). Additional evidence highlights the impact of cultural context on beliefs about trauma, PTSD, and recovery (e.g., Bryant-Davis, 2019).…”
Section: Limitations Future Directions and Constraints On Generalitymentioning
confidence: 99%